Speciálněpedagogická diagnostika logopedická Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Chleboradová, Barbora (Masaryk University Press, 2019)
Title in English: Diagnostics in the Field of Speech Therapy: Methodical texts for the MUNI 4.0 project The study support is focused on the issue of indicative assesment of communication skills in preschool children - in accordance with the objectives and specialization of the bachelor study. The text presents selected technical terminology, tasks, procedures and alternatives of the use of verbal and visual material for indicative assesment of language levels. For an overview, examples of tests and materials applied in our practice are presented to familiarize the students with the structure and principles of these tasks. The text also includes topics of cooperation with the child, parents and structuring and processing of acquired findings.